Multimodal assessment of estrogen receptor mRNA profiles to quantify estrogen pathway activity in breast tumors - Muthukaruppan, Anita; Lasham, Annette; Woad, Kathryn J.; Black, Michael A.; Blenkiron, Cherie; Miller, Lance D.; Harris, Gavin; McCarthy, Nicole; Findlay, Michael P.; Shelling, Andrew N.; Print, Cristin G. (Elsevier, 2017)
Background